2014
DOI: 10.1007/s00167-014-2983-8
|View full text |Cite
|
Sign up to set email alerts
|

Knee flexion after total knee arthroplasty reduces blood loss

Abstract: Knee flexion at 90° after TKA, associated with the intraoperative use of tranexamic, acid is an effective method to reduce blood loss and the need for blood transfusion. The routine use of the present protocol is effective in reducing social costs and length of hospitalization of TKA procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 25 publications
3
29
0
2
Order By: Relevance
“…Johnson has reported that knee flexion following TKA might increase wound complications by lowering oxygen tension in the wound edges [28]. Eight of the included studies [11, 14, 16, 18–22] mentioned these complications while the remaining two failed to do so [15, 17], and our study did not find any difference in wound complications between the two groups (Table 3). …”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…Johnson has reported that knee flexion following TKA might increase wound complications by lowering oxygen tension in the wound edges [28]. Eight of the included studies [11, 14, 16, 18–22] mentioned these complications while the remaining two failed to do so [15, 17], and our study did not find any difference in wound complications between the two groups (Table 3). …”
Section: Discussionsupporting
confidence: 43%
“…There were no significant inter-group differences with regard to age, gender and body mass index (BMI). The baseline level of hemoglobin [11, 14, 17–19, 21, 22] and ROM [11, 14, 20, 22] were well balanced between the flexion group and extension group in some studies. Three RCTs were excluded due to various reasons.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis has indicated that the intra-articular injection of a high dosage of TXA (30 mg/ml) may reduce the total blood loss and the requirement of blood transfusions. Knee flexion at 90 after TKA with the intraoperative use of TXA is an effective method to reduce blood loss and the need for blood transfusions [18].…”
Section: Discussionmentioning
confidence: 99%